2018
DOI: 10.1002/jrs.5511
|View full text |Cite
|
Sign up to set email alerts
|

Development of a headspace solid‐phase microextraction–surface‐enhanced Raman scattering approach to detect volatile pesticides

Abstract: By coupling headspace solid‐phase microextraction (HS‐SPME) with surface‐enhanced Raman scattering (SERS), a facile and rapid method was developed for the detection of organophosphorus insecticides (phorate and isocarbophos) and organic sulfur bactericide (ferbam) in the vapour phase. Two types of SPME fibres based on stainless steel wires coated with gold (Au) nanoparticles were prepared. The fibre (Fibre II) prepared by an etching approach showed better sensitivity than did the fibre (Fibre I) prepared using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The main characteristic vibration bands of tricyclazole stem from the C‐N‐C bending (429 cm −1 ), C‐C bending (561 cm −1 ), C‐S‐C bending (595 cm −1 ), C=C stretching (974 cm −1 ), and C‐N stretching (1,310 cm −1 and 1,374 cm −1 ), respectively . The major characteristic bands of isocarbophos at wavenumber of 850 cm −1 and 1,041 cm −1 are attributed to P=S stretching and ortho‐substituted benzene ring stretching …”
Section: Resultsmentioning
confidence: 99%
“…The main characteristic vibration bands of tricyclazole stem from the C‐N‐C bending (429 cm −1 ), C‐C bending (561 cm −1 ), C‐S‐C bending (595 cm −1 ), C=C stretching (974 cm −1 ), and C‐N stretching (1,310 cm −1 and 1,374 cm −1 ), respectively . The major characteristic bands of isocarbophos at wavenumber of 850 cm −1 and 1,041 cm −1 are attributed to P=S stretching and ortho‐substituted benzene ring stretching …”
Section: Resultsmentioning
confidence: 99%
“…This newly designed approach may greatly improve the practical application of SERS detection in environmental monitoring, medicine, and food safety, especially in resource‐limited environments. Wang et al [ 24 ] reported development of a headspace solid‐phase microextraction‐SERS approach to detect volatile pesticides. They found that their approach can be extended to detect a wide range of volatile organics and shows potential as an easier and faster alternative to gas chromatography for studying volatile chemicals in some cases.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…23 By coupling with pretreatment equipment such as headspace solid-phase microextraction (HS-SPME), Wang et al developed a SERS method to detect three vapor-phase pesticides as low as 0.02 ppm. 24 However, these approaches still have the problems of tedious and time-consuming procedures, which may be not suitable for rapid screening and field detecting. An alternative approach to achieve SERS detection for gaseous samples is to utilize nanoporous material substrates 25 or to coat a sorptive shell like MOFs 26 on the surface of the nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…−80 °C) for enhancing the adsorption of target molecules on the SERS substrate . By coupling with pretreatment equipment such as headspace solid-phase microextraction (HS-SPME), Wang et al developed a SERS method to detect three vapor-phase pesticides as low as 0.02 ppm . However, these approaches still have the problems of tedious and time-consuming procedures, which may be not suitable for rapid screening and field detecting.…”
Section: Introductionmentioning
confidence: 99%